OPEN PERFORATION OF MAXILLA ALVEOLAR SPROUT, PERFORATION OF THE TOOTH CAVITY BOTTOM AT ENDODONTIC TREATMENT OF THE FIRST MOLAR ON MAXILLA (CLINICAL CASE) - T.P. Skripnikova; Т.А. Khmil; S.V. Bilous (Ukrainian Medical Stomatological Academy, 2018)
The paper presents a clinical issue of multiple doctor's errors when he/she performs endodontic treatment. Injection needle defects that caused perforation in the bone tissue of the alveolar process, partial preparation of the tooth cavity, loss of the cheek, medial root canal, perforation of the bottom of the tooth cavity were revealed. As a result, errors caused complications. A corresponding medical-prophylactic complex was completed with a successful result.